(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
Rainwater Harvesting is the accumulation and storage of rain water for reuse on site, rather than allowing it to runoff. The harvested water can be used as drinking water, longer term storage and to recharge ground water. A proposal for rain water harvesting for ground water recharge for Dr. D. Y. Patil Institute of Technology, Pimpri (DIT) has been prepared by studying all required parameters at site. Cost estimation of the proposed work has been done in detail. Implementation of the method has been done at one of the four proposed locations. In this paper the proposed work at DIT, cost estimation and actual work at site has been presented.